Bcl-2 antagonist apogossypol (NSC736630) displays single-agent activity in Bcl-2–transgenic mice and has superior efficacy with less toxicity compared with gossypol (NSC19048) - Kitada, Shinichi (American Society of Hematology, 2008)
Altered expression of Bcl-2 family proteins plays central roles in apoptosis dysregulation in cancer and leukemia, promoting malignant cell expansion and contributing to chemoresistance. In this study, we compared the toxicity and efficacy in mice of natural product gossypol and its semisynthetic derivative apo-gossypol, compounds that bind and inhibit antiapoptotic Bcl-2 family proteins. Daily oral dosing studies showed that mice tolerate doses of apogossypol 2- to 4-times higher than gossypol. Hepatotoxicity and gastrointestinal toxicity represented the major adverse activities of gossypol, with apogossypol far less toxic. Efficacy was tested in transgenic mice in which Bcl-2 is overexpressed in B cells, resembling low-grade follicular lymphoma in humans. In vitro, Bcl-2–expressing B cells from transgenic mice were more sensitive to cytotoxicity induced by apogossypol than gossypol, with LD50 values of 3 to 5 μM and 7.5 to 10 μM, respectively. In vivo, using the maximum tolerated dose of gossypol for sequential daily dosing, apogossypol displayed superior activity to gossypol in terms of reducing splenomegaly and reducing B-cell counts in spleens of Bcl-2–transgenic mice. Taken together, these studies indicate that apogossypol is superior to parent compound gossypol with respect to toxicology and efficacy, suggesting that further development of this compound for cancer therapy is warranted.